Parte I: Anatomía microquirúrgica tridimensional de la ínsula - Gustavo, Gustavo; Campero, Alvaro; Ajler, Pablo; Edgar Manuel, Edgar Manuel; Thomas M., Thomas M.; Infantini Dini, Leandro (Revista Argentina de Neurocirugía, 2020)
Introduction: The insular lobe, or insula, is the cerebral lobe sitting deep in the sylvian fissure and hidden by the lateral surface of the brain. It is covered by the frontal, parietal and temporal operculum. Objectives: To study the anatomy of the insular lobe, one of the most complex parts of the human brain, and to correlate this anatomy with intraoperative findings. Materials and Methods: In the first part of this article we show the results of our dissections, documented in 2D and 3D, and focus on microsurgical anatomy. In the second part we correlate the anatomical structures with intraoperative findings from 44 insular tumor surgeries, mainly gliomas, of patients operated on from 2007 to 2014. Results: Huge bundles of subcortical fibers, like uncinate, inferior fronto-occipital and arcuate fascicles, connect the insula to the neighboring structures. Several anatomical structures related to neurological disabilities are closely related to insular surgery, like the middle cerebral artery, internal capsule, lenticulostriate arteries and cortical and subcortical language circuits. Conclusions: Microsurgical laboratory training, 3D documentation, knowledge of brain mapping and modern neurosurgical armamentarium are important factors in achieving good results with insular glioma tumors.